Phosphorylation regulates functions of ZEB1 transcription factor - Llorens de Los Ríos, María Candelaria (2016)
ZEB1 transcription factor is important in both development and disease, including many TGFβ-induced responses, and the epithelial-to-mesenchymal transition (EMT) by which many tumors undergo metastasis. ZEB1 is differentially phosphorylated in different cell types; however the role of phosphorylation in ZEB1 activity is unknown. Luciferase reporter studies and electrophoresis mobility shift assays (EMSA) show that a decrease in phosphorylation of ZEB1 increases both DNA-binding and transcriptional repression of ZEB1 target genes. Functional analysis of ZEB1 phosphorylation site mutants near the second zinc finger domain (termed ZD2) show that increased phosphorylation (due to either PMA plus ionomycin, or IGF-1) can inhibit transcriptional repression by either a ZEB1-ZD2 domain clone, or full-length ZEB1. This approach identifies phosphosites that have a substantial effect regulating the transcriptional and DNA-binding activity of ZEB1. Immunoprecipitation with anti-ZEB1 antibodies followed by western analysis with a phospho-Threonine-Proline-specific antibody indicates that the ERK consensus site at Thr-867 is phosphorylated in ZEB1. In addition to disrupting in vitro DNA-binding measured by EMSA, IGF-1-induced MEK/ERK phosphorylation is sufficient to disrupt nuclear localization of GFP-ZEB1 fusion clones. These data suggest that phosphorylation of ZEB1 integrates TGFβ signaling with other signaling pathways such as IGF-1.